(untitled) (Universal International Scientific Journal, 2026)
The article analyzes the effectiveness of interactive methods in developing critical thinking in students from a scientific and pedagogical perspective. The theoretical foundations of interactive educational technologies, the mechanisms of their influence on the cognitive process, and their role in activating the analytical and reflective activities of students are highlighted. The study substantiates the positive impact of the educational process, organized on the basis of discussion, debate, problem situations, and reflective tasks, on the quality of education.